Bipolarity among pregnant women at King Chulalongkorn Memorial Hospital and relationship with depression score during pregnancy and postpartum periods - Siripalanon, Ratsamimarn; Roomruangwong, Chutima (Chulalongkorn Medical Journal, 2020)
Background: Previous studies demonstrated associations between bipolarity and perinatal depression. However, there is still no study on this issue in Thailand. Objectives: To examine the prevalence of bipolarity and associations with depressive symptoms during pregnancy and postpartum periods. Methods: We recruited 165 pregnant women who were in their third trimester (gestational age 28 weeks). The self-rated questionnaires used include the Edinburgh Postnatal Depression Scale (EPDS) - Thai version, Mood Disorder Questionnaire scales (MDQ) - Thai version, the Personal Resource Questionnaire (PRQ)- Part II and the Dyadic Adjustment Scale (DAS). Then we followed up EPDS scores at 2 - 7 days after delivery. Univariate and multivariate statistics were used to examine the associated factors of bipolarity. Results: The prevalence of bipolarity was 3%. Unemployment, inadequacy of income, history of lifetime smoking, and smoking during pregnancy, were found to be significantly associated with bipolarity (P < 0.05). Bipolarity was also associated with lower PRQ scores (assistance and guidance subscale) and lower marital satisfaction scores (dyadic cohesion subscale) (r = 0.507, P < 0.05). Moreover, bipolarity was also associated with higher EPDS total score during pregnancy, and in the item of anxiety/ worry, sad/ miserable, crying, and suicidal thoughts, lower PRQ scores (social integration subscale), lower marital satisfaction scores (dyadic satisfaction subscale), higher marital satisfaction scores (dyadic consensus subscale) when compared to those without bipolarity (P < 0.01). Conclusions: The prevalence of bipolarity in this study is somewhat higher than in the general population. Bipolarity was significantly associated with substance abused during pregnancy, poorer functions (work/ financial), higher severity of antenatal depression, especially in the symptoms of anxiety/ worry, sad/ miserable, crying, and suicidal thoughts. They also significantly have lower social support and lower marital satisfaction when compared to those without bipolarity.